Los mecanismos de cobro tipificado en el artículo 69 numeral 1 del código orgánico integral penal respecto de las multas establecidas en el artículo 70 ibidem inciden en la resocialización del pospenado - Rosario Miranda, Juan Carlos (2024)
The general objective of the research carried out is to determine the collection mechanisms typified in article 69, paragraph 1 of the Organic Comprehensive Criminal Code, with respect to the fines established in article 70 ibid., which affect the resocialization of the post-convict, for which the concept of fine is analyzed as the typical patrimonial penalty, and its relationship in the process of resocialization of people sentenced for the commission of a crime. A methodology of documentary analysis has been used that has allowed the review of the literature on criminal matters, both national and foreign, in order to reach conclusions, such as the need to broaden the purpose of the penalty, since if only the rehabilitative and resocializing effect is taken into account, it seems to cover only the deprivation of liberty; However, if we think about the function of ensuring the protection of the individual, the patrimonial penalty turns out to be adequate.